ANALISIS PEMANFAATAN TEKNOLOGI SISTEM TANAM JAJAR LEGOWO 2:1 PADA USAHATANI PADI SAWAH DI DESA TOBURI KECAMATAN POLEANG UTARA KABUPATEN BOMBANA - Jumasni Jumasni; La Nalefo; Mardin Mardin (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2022)
This studied aim to determined the use of jajar legowo 2: 1 planting system technology in pafarming in Toburi Village, North Poleang District, Bombana Regency. To The determination of the research area was determined purposively with the consideration that one of the areas whose farmers used the jajar legowo 2:1 planting system technology in processing paddy rice farming. There were 30 respondents who applied the 2:1 legowo jajar planting system technology. Data analysis using qualitative analysis. The results showed that 30 farmers who utilized the legowo 2:1 jajar planting system technology were able to be adequate for the development of their farming business, several stages of the process carried out by farmers in utilizing the legowo 2:1 jajar planting system technology include: Land processing process, seedling process, planting process, embroidery process, maintenance process, fertilization process, pest and disease control process, and harvesting process.